Antimicrobial activity of leaf extracts and isolated constituents of Croton linearis. (23rd May 2019) - García Díaz, Jesús; Tuenter, Emmy; Escalona Arranz, Julio Cesar; Llauradó Maury, Gabriel; Cos, Paul; Pieters, Luc
Abstract: Ethnopharmacological relevance: Leaves of Croton linearis, known as "rosemary", are widely used in folk medicine in Caribbean countries to treat fever and colds (associated to infections). Aim of the study: To evaluate the in vitro antimicrobial activity of extracts and fractions derived from C. linearis leaves. Materials and methods: Bioassay-guided fractionation and isolation of compounds from an ethanolic extract of C. linearis, using flash chromatography and semi-preparative HPLC-DAD-MS (High Performance Liquid Chromatography – Diode Array Detection – Mass Spectrometry). Isolated compounds were characterized by MS, 1D- and 2D-NMR (Nuclear Magnetic Resonance) spectroscopy. The microdilution method with resazurin, as well as direct counting with an optical microscope, were used to determine the in vitro antimicrobial activity against bacteria, fungi and parasites. Moreover, the cytotoxicity on human fetal lung fibroblasts (MRC-5) was evaluated. Results: The total extract and chloroform fraction (ClF) showed high activity against protozoa with IC50 values ranging from 1 to 26 μg/mL, but also cytotoxicity on MRC-5 and PMM (Peritoneal Murine Macrophages). Seven compounds were isolated and characterized for first time in this species: the alkaloids laudanidine, laudanosine, reticuline, corydine, glaucine and cularine and the flavonoid glycoside isorhamnetin-3- O -(6″ O - p - trans -coumaroyl)- β -glucopyranoside. Reticuline showed a weak activity against L. infantum (IC50 148.0 ± 1.2 μM), while the flavonoid was active against T. cruzi (IC50 35.6 ± 2.3 μM). Conclusions: The results show the antiprotozoal potential of the extract and some isolated constituents, which supports the use of this species in Caribbean folk medicine. Graphical abstract: Image 1